Goats as seed dispersers: contributions and limitations for the regeneration of the seasonally dry tropical forest in Ecuador - Espinosa, Carlos I.; Reyes, Carlos; Jara-Guerrero, Andrea (Revista de Biología Tropical, 2021)
Introduction: Seasonally dry tropical forests are subject to chronic degradation processes, which has reduced the populations of some important animal dispersers. Intensive livestock farming within the forest remnants is considered one of the main causes of these degradation processes. However, domestic ungulates could also be fulfilling the role of seed dispersal for some wild species. Objective: To evaluate the role of goats as seed dispersers of woody species and the possible consequences of their feeding behavior on the vegetation structure. Methods: Between December 2016 and June 2017, we collected goat feces from pens (N = 38) and vegetation plots (N = 42) from three locations of dry forest in the Southwestern Ecuador. All the seeds found in the feces (N = 13 326) were recorded and taxonomically identified. To evaluate the effect of gut passage on seed germination, we sowed the seeds found in the goat feces from the pens and seeds collected directly from parent plants. Results: Goats dispersed seeds from ten species, of which at least 50 % are legumes. Acacia macracantha seeds represented ca. 70 % of seeds present in goat feces. The passage of seeds through the digestive tract of goats significantly improved the percentage and speed of germination in Albizia multiflora, Piscidia carthagenensis and Ziziphus thyrsiflora, while in Choroleucon mangense and Prosopis juliflora no germination was registered. We did not find a correlation between the richness of established trees and the number of species found in the goat feces (χ2 = -0.23, P = 0.53). The composition of dispersed seed species in the feces did not show a dependency on the locality, although the composition of the established vegetation changes between localities. The frequency of seeds in the feces did not show a relationship with the tree abundance in the established vegetation. Conclusions: Goats can play, at least partially, the role of locally extinct wild ungulates, improving the germination of legume species with hard coat. However, this positive effect can be blurred by their feeding behavior and high preference for particular species, which can modify the dominance of some species, and result in changes in the composition and structure of the vegetation.